ANALYSIS THE IMPACT OF SOCIAL NETWORKING SITES (SNW’S) ON JOB SEEKERS IN MANADO - Lasari, Sri Handayani Yuyun; Massie, James D.D; Pandowo, Merinda . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: Social networking Web sites are nowadays considered the most popular Web sites on the Internet. Moreover, they appear to be an increasingly useful tool for human resource management professionals to advertise job openings and seek information about job seekers in an efficient and cost-effective way. The aim of this study is to analyze impact of Social Networking Sites (SNW’s) on Job Seekers in Manado. To achieve these objectives the researcher got information from 10 respondents using qualitative study which is in-depth interview and uses purposive sampling and snowball sampling. The results showed that Social Networking Sites (SNW’s) gives a positive impact to all the respondent Social Networking Sites (SNW’s) become an important role for all the job seekers because Social Networking Sites’s is very easy to use, very understandable and also there are a lot of information about job recruitment, job application, the job seekers can see all the company or the instituion that has open the recruitment. The recommendation for the next Job Seekers that will use Social Networking Sites, it wil be more complete if all the Job seekers explore and more about all the positive impact, because nowadays Internet become an important role for the job seekers as an alternative way to find a job. Keywords: social networking sites, job seekers